HIC2 is a novel dosage-dependent regulator of cardiac development located within the distal 22q11 deletion syndrome region - Dykes, IM; van Bueren, KL; Ashmore, RJ; Floss, T; Wurst, W; Szumska, D; Bhattacharya, S; Scambler, PJ (American Heart Association, 2014)
Rationale: 22q11 deletion syndrome arises from recombination between low-copy repeats on chromosome 22. Typical deletions result in hemizygosity for TBX1 associated with congenital cardiovascular disease. Deletions distal to the typically deleted region result in a similar cardiac phenotype but lack in extracardiac features of the syndrome, suggesting that a second haploinsufficient gene maps to this interval.